2018
DOI: 10.1186/s12885-018-4858-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary spontaneous pneumothorax in patients with sarcoma treated with Pazopanib, a case control study

Abstract: BackgroundThe tyrosine kinase inhibitor pazopanib is used for treatment of sarcoma. Recent studies have suggested that the use of pazopanib may lead to the development of pneumothorax, an unexpected adverse effect in patients with sarcoma metastatic to the chest.MethodsWe conducted a retrospective case control study of patients with sarcoma with metastases to the chest with pneumothorax (cases) and without pneumothorax (controls). The control population was selected from tumor registry in a 1:4 (cases to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In addition, Nakano et al found that risk factors for pneumothorax in patients with STS lung metastases during pazopanib treatment were lung metastases with a ≥30-mm maximum diameter and the presence of a history of pneumothorax before pazopanib treatment (6). In contrast, a recent case control study suggested that pazopanib did not increase the risk of pneumothorax in patients with lung metastases from STS (8). However, that study had several limitations, one being that the odds of developing pneumothorax in patients with STS on pazopanib were retrospectively analyzed using a purposeful selection method.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, Nakano et al found that risk factors for pneumothorax in patients with STS lung metastases during pazopanib treatment were lung metastases with a ≥30-mm maximum diameter and the presence of a history of pneumothorax before pazopanib treatment (6). In contrast, a recent case control study suggested that pazopanib did not increase the risk of pneumothorax in patients with lung metastases from STS (8). However, that study had several limitations, one being that the odds of developing pneumothorax in patients with STS on pazopanib were retrospectively analyzed using a purposeful selection method.…”
Section: Discussionmentioning
confidence: 90%
“…Sabath et al. have identified pre-treatment cavitation (odds ratio [OR] = 7.0, p<0.001) and pleural or base location of lung nodules (OR = 10.4, p<0.001) as independent risk factors ( 77 ). Nakano et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the exact reasons for the discrepancy are unknown. Pazopanib is another multitarget TKI that has a high probability of causing pneumothorax in patients with sarcomas [8,17,18]; the targets of pazopanib are also different from those of apatinib (Table 3) [19]. Different targets result in different effectiveness of the two TKIs for osteosarcoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These TKIs inhibit a variety of tyrosine kinases, and although their multitarget nature has led to effective treatment of osteosarcoma, it has also caused various adverse events. A growing number of studies have shown that pneumothorax is one of adverse events (AEs) associated with treatment of sarcomas using multitarget TKIs [5,8,9].…”
Section: Introductionmentioning
confidence: 99%